The chemical characterization and tectonic significance of ophiolite terrains in southeastern Papua New Guinea. Issue 2 (26th April 2013) - Smith, Ian E. M.
Abstract [1] The evolution of the southeastern Gondwana margin in the Papua New Guinea segment is manifested by ophiolites signifying plate collision, volcanic arcs marking subduction, and metamorphic core complexes that have developed during extensional events and exhumation associated with sea floor spreading in the Woodlark Basin to the east. In detail the Papuan Ultramafic Belt marks a well‐documented collision between continental crust and a subduction system. However, to the southeast, an extensive sequence of basaltic rocks known as the Milne Terrain is more problematic. Geochemical data indicate that these upper Cretaceous and Eocene rocks have MORB‐type affinities, and their most likely tectonic association is with the opening of the Coral Sea Basin. Milne Terrain rocks represent the lower plate in the obduction system along which the Papuan Ultramafic Belt was emplaced, and thus they are the structural equivalent of the continental crust which was separated from the Australian continental block by the opening of the Coral Sea. Spectacular uplift (>4 km) of the oceanic basaltic crust of the Milne Terrain may be due to the underlying presence of underplated material associated with a Late Miocene‐Pliocene episode of subduction immediately prior to the encroachment of the Woodlark spreading center into the Papuan area.